'Optimal thermal range' in ectotherms: Defining criteria for tests of the temperature-size-rule. (August 2016) - Walczyńska, Aleksandra; Kiełbasa, Anna; Sobczyk, Mateusz
Abstract: Thermal performance curves for population growth rate r (a measure of fitness) were estimated over a wide range of temperature for three species: Coleps hirtus (Protista), Lecane inermis (Rotifera) and Aeolosoma hemprichi (Oligochaeta). We measured individual body size and examined if predictions for the temperature-size rule (TSR) were valid for different temperatures. All three organisms investigated follow the TSR, but only over a specific range between minimal and optimal temperatures, while maintenance at temperatures beyond this range showed the opposite pattern in these taxa. We consider minimal and optimal temperatures to be species-specific, and moreover delineate a physiological range outside of which an ectotherm is constrained against displaying size plasticity in response to temperature. This thermal range concept has important implications for general size-temperature studies. Furthermore, the concept of 'operating thermal conditions' may provide a new approach to (i) defining criteria required for investigating and interpreting temperature effects, and (ii) providing a novel interpretation for many cases in which species do not conform to the TSR. Highlights: The question on the thermal limits for size-to-temperature response (TSR) was posed. The thermal performance curves for fitness were examined for three aquatic species. The concept of 'operating thermal conditions' for TSR was proposed. This concept was validated based on the dataset of previously published studies. This approach defines criteria for investigating and interpreting temperature effects.